Dentists’ Preferences in the Treatment of Congenitally Missing Maxillary Lateral Incisors - Abdulrahman, Nuha Abdulazeem Mohammed; Khalifa, Nadia; Alhajj, Mohammed Nasser (Brazilian Dental Science, 2019)
Objective: Congenitally missing maxillary lateral incisors present challenges to dentists in terms of treatment planning and can negatively affect aesthetics and function in patients. The aim of the present study was to determine the preferred treatment approach of dentists with different specialties. Material and Methods: We carried out a descriptive, cross-sectional study using a questionnaire that was self-administered to 12 specialists in removable prosthodontics, 18 specialists in restorative dentistry, 14 specialists in orthodontics, and 173 registered general dentists. Results: General practitioners (72.7%), prosthodontists (92.9%) and, restorative dentists (80%) preferred prosthodontic replacement of missing maxillary lateral incisors, while orthodontists (57.1%) preferred canine substitution. Most general practitioners (62.7%), prosthodontists (71.4%), and orthodontists (92.9%), as well as many restorative specialists (40%), preferred implant-retained crowns for prosthetic replacement of missing lateral incisors. The dental specialties differed significantly in terms of their preferred modalities for treating children over the age of 12 years. General practitioners (56%) preferred removable partial dentures (RPDs), while a mere 17.2% preferred to carry out no treatment. All prosthodontists (100%) preferred treatment with RPDs. Restorative dentists preferred RPDs and adhesive bridges in equal number (33.3% in each case). Fifty percent of orthodontists treating children with missing lateral incisors preferred RPDs, followed by (28.6%) who preferred canine substitution. Conclusion: Preference varied for several reasons among dentists’ treating both adults and children over 12 years of age. Keywords Maxillary missing teeth; Dentist’s preference; Teeth replacement; Dental implant.